Pengaruh Return on Assets, Current Ratio dan Firm Size Terhadap Prediksi Kebangkrutan Dengan Struktur Modal sebagai Variabel Moderasi - Mita Ayu Safitri; Indah Yuliana (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2021)
This study aims to determine: the prediction results of bankruptcy in basic and chemical industry companies listed on the IDX for the 2016-2019 period and to determine the effect of return on assets, current ratio and company size on financial distress. Based on the purposive sampling method, there were 38 companies sampled. The method of analysis used is descriptive statistical method using Moderated Regression analysis tools. The results of this study indicate that the current ratio has a significant positive effect on financial distrees. Return on assets and company size have no effect on financial distrees. Capital structure is able to moderate the relationship between return on assets and financial distress. The capital structure is unable to moderate the relationship between current ratios and company size to financial distress in basic industrial and chemical companies. By using the Grover model, it can be that of the thirty eight samples all companies have no potential.